A new species of Esagonatopus Olmi (Hymenoptera, Dryinidae) from Central Brazil - Martins, André Luis (Zootaxa, 2018)
Esagonatopus antonioi Martins sp. nov. from Central Brazil is described and illustrated. The new species is characterized by having the head slightly excavated, almost flat, with granulate sculpture; the frontal line complete; the occipital carina absent; the mesosoma reticulate rugose and the scutum without lateral pointed apophyses. An updated key to the Neotropical species of the genus Esagonatopus Olmi is provided.